ANALISIS PENGGUNAAN JARINGAN FIBER OPTIK DI AREA KAWASAN BIJB KERTAJATI - Muhammad Ridhwan; Lela Nurpulaela (Jurnal Ilmiah Wahana Pendidikan, 2023)
Fiber optic is a type of network that allows the transmission of light as a substitute for the electrical signals used by other types of networks that use copper. Although relatively expensive, optical fiber has a longer range from 550 meters to hundreds of kilometers, and is capable of transmitting data at higher speeds than other types of networks. Optical fiber is also resistant to electromagnetic interference. To transmit information, signal bits are converted into light before being sent through the optical fiber. The use of the network as a transmission medium in the BIJB Kertajati area is a very important aspect, its use is used on almost all electronic devices that require a network connection as a transmission medium and information in real time. Devices that require a network in the area area are CCTV, CCTV functions to monitor the surrounding conditions in real time 24 hours. The network system used is a Fiber Optic network that is connected from the server room to each area Switch Area rack in the SS (Sub Station) building throughout the area there are 9 SS and 87 camera points. It can also be seen that each FO network cable has a different number of cores where the difference in the number of cores affects the number of cameras that can be connected. 1 camera requires 2 FO cores (TX/RX). The data transfer speed carried is affected by the type of switch and SFP installed.